Soil Structure in Everglades Agricultural Area Histosols: Effects on Carbon Sequestration and Subsidence - Alan L. Wright; Edward A. Hanlon (EDIS)
SL-301, a 6-page illustrated fact sheet by A. L. Wright and E. A. Hanlon, discusses organic soil oxidation relative to storing or releasing carbon and nitrogen, evaluates effects of cultivation, and uses this information to predict long-term outcomes for agricultural production and reclamation. Includes additional sources of information. Published by the UF Department of Soil and Water Science, August 2009.